Historical perspectives on East Asian science, technology, and medicine - Chan, Alan Kam-leung; Clancey, Gregory K.; Loy, Hui-Chieh (Singapore University Press, National University of Singapore World Scientific, 2001)
Historical Perspectives on East Asian Science, Technology, and Medicine brings together over fifty papers by leading contemporary historians from more than a dozen nations. It is the third in a series of books growing out of the tri-annual International Conference on the History of Science in East Asia, the largest and most prestigious gathering of scholars in the field. The current volume broadens the field's traditional focus on China to include path-breaking work on Vietnam, Korea, Japan, the Philippines, and even the transmission of Asian science and technology to Europe and the United States. Topics covered include: traditional Chinese, Vietnamese, and Filipino medicines; Chinese astronomy; Japanese earthquakes; science and technology policy; architecture; the digital revolution; and much else.